Autonomous decentralized systems and their applications in transport and infrastructure - Mori, Kinji, 1947-; Kunifuji, Takashi (IET transportation series ;, 2018)
The ADS (autonomous decentralized system) concept proposed in 1977 has been progressed and advanced in technologies of control, communication and computer in these 40 years. The technologies have been continuously applied to the various `engineering' fields such as manufacturing, transportation, utility and information. These applications in the real world have been operated well, and they show the effectiveness of the ADS systems. ADS has been persistently advanced in cooperation with the international group including industries, universities and public sectors. The book is organized in four parts. Part 1: Introduction - paradigm shift by ADS; Part 2: Infrastructure - infrastructure of engineering systems of railway, air traffic, manufacturing; Part 3: Life - ticketing service, robotic service, information service, social service; Part 4: Business - blockchain, bank, railway service, smart system.